ANALISIS ISI FITUR INSTAGRAM STORIES SEBAGAI MEDIA KOMUNIKASI INTERPERSONAL PENGGUNA INSTAGRAM DI KOTA MAKASSAR - Hikmah Indriani , Nur; Zelfia, Zelfia (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
The objectives of this study are, How is the description of Interpersonal Communication that occurs in Instagram users in Makassar City. How to Fill in the Instagram Stories Feature for Instagram users in Makassar City. This research lasted for one month with 4 (four) informants, where all of the informants were Instagram users who often used the question sticker feature on Instagram stories. The research method used is descriptive qualitative content analysis method, with data collection techniques carried out in two ways, namely primary and secondary data. The method of data collection by conducting observations, interviews, and documentation.